Evaluating the Decision to Adopt RFID Systems Using Analytic Hierarchy Process - Lin, K.; Lin, Chad (The Journal of American Academy of Business, 2007)
Interests continue to grow in recent years for the adoption of Radio Frequency IDentification (RFID) technologies due to their capability for real-time identification and tracking. A good example of this was when Wal-Mart asked its top 100 suppliers to use RFID tags in 2005. This had a profound effect on the projected growth of RFID technology as well as potential applications in industries such as defense, wholesale, and retail. However, there are some business and technical problems and issues with the use of RFID technologies (such as data accuracy, costs and benefits, and security and privacy) and these warrant further research. Thus, this research aims to establish a decision analysis mechanism that can assist organizations to judge if they are suitable to adopt the RFID systems. The AHP (Analytic Hierarchy Process) methodology is employed to analyze the RFID adoption decision processes of both RFID expert and industry evaluators.